Eksplorasi Perilaku Keuangan Gen Z Dalam Menggunakan E-wallet Sebagai Bentuk Adaptasi Terhadap Cashless Society Mahasiswa Universitas Muhammadiyah Makassar - Nurhikmah SR; Wa Ode Rayyani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study explores the financial behavior of Generation Z students in using e-wallets as a form of adaptation to a cashless society. The study employed a descriptive qualitative method with data collected through in-depth interviews involving five students from Universitas Muhammadiyah Makassar who actively use e-wallets. The findings show that students are attracted to e-wallets due to convenience, fast transactions, and promotional rewards such as cashback. However, many of them display impulsive buying behavior, lack financial planning, and do not keep records of their expenses. Furthermore, digital security awareness is still low, as most respondents do not apply preventive measures such as two-factor authentication. The cashless-supportive environment on campus also contributes to their daily digital payment habits. This research recommends implementing digital financial literacy programs and raising awareness on digital security risks to encourage wiser and safer e-wallet usage among Gen Z students.